Tradisi Go Ge Cap Lak (Bakar Tongkang) Dalam Tinjauan Sosiologi Ekonomi Islam - Candra, Kavita Lovia; Efrianti, Esti; Purwanto, Muhamad Aji (Journal of Islamic Economics (JoIE), 2023)
Introduction: Go Ge Cap Lak, according to the Chinese community, has the meaning of expressing gratitude to Kie Ong Ya (the god of the sea) who has given protection to their ancestors when sailing the ocean so that they can reach the Rokan Hilir region. In the course of its history, Go Ge Cap Lak in addition to having theological value also has a very thick anthropocentric value that makes the tradition as one of the religious tourism in the region. Not only the ethnic Chinese community benefited but also Muslims who lived in the local area. This tradition has become an annual event with a considerable economic impact. However, what if this tradition is seen in the study of Islamic economic sociology Research Methods: This research is included in the type of field research with qualitative descriptive data analysis methods. Primary data sources come from data mining in the field and supporting sites such as disbudpora, while secondary data sources come from previous research Results: The tradition has an economic impact on the surrounding Muslim community. This expediency is in line with the orientation of fulfilling life or in the language of religion in order to maintain life. Conclusion: Go Ge Cap Lak also has economic value. The Ministry of Tourism and Creative Industries includes Go Ge Cap Lak as one of the annual activities that are always held in Bagansiapiapi. This activity also made the economy of the Bagansiapiapi Muslim community rise and develop.